PENGEMBANGAN SKALA LOCUS OF CONTROL - Hendryadi, Hendryadi (Economic Faculty, Attahiriyah Islamic University, 2017)
This article aims to develop a short form of the locus of control scale. The study was conducted in two stages: a study of 66 respondents as pilot testing which aims to test content validity, structure validity, and internal consistency. Study 2 was conducted on 328 respondents used to test the validity and reliability of the scale evaluated by the PLS-SEM method (such as internal consistency, convergent validity, and discriminant validity). The analysis concludes that the 8-item locus of control scales tested have adequate validity and reliability. A short form locus of control scale was developed and validated in this study, so it can be used in future research and evaluation for HR management practitioners in employee selection Keywords: locus of control, EFA, CFA, scale construction